2021
DOI: 10.1017/s1463423621000074
|View full text |Cite
|
Sign up to set email alerts
|

Management of chronic kidney disease: perspectives of Brazilian primary care physicians

Abstract: Aim: To investigate primary care physicians’ knowledge of and attitudes toward care for chronic kidney disease patients. Background: In Brazil, care for chronic kidney disease, a global public health problem, is provided by the Brazilian National Health System, which is organized around primary care. The study aimed to investigate the knowledge and attitudes of primary care physicians about the management of chronic kidney disease. Method: This research is based on quan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 24 publications
0
5
0
5
Order By: Relevance
“…Approximately two-thirds of the participants in our study did not adhere to CKD guidelines in their clinical practice. A study conducted among Brazilian primary care physicians revealed that half of the physicians were unaware of the national CKD guidelines [ 15 ]. Another study conducted in West Africa among FM and non-nephrologist IM physicians found that 37% of them were unaware of any guidelines for the management of CKD, and only 28% were aware of the Kidney Disease Outcome Quality Initiative (KDOQI) guidelines for CKD management [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Approximately two-thirds of the participants in our study did not adhere to CKD guidelines in their clinical practice. A study conducted among Brazilian primary care physicians revealed that half of the physicians were unaware of the national CKD guidelines [ 15 ]. Another study conducted in West Africa among FM and non-nephrologist IM physicians found that 37% of them were unaware of any guidelines for the management of CKD, and only 28% were aware of the Kidney Disease Outcome Quality Initiative (KDOQI) guidelines for CKD management [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Estudo que traçou o panorama do cuidado às pessoas com DRC, a dosagem sérica de creatinina é solicitada por grande parte dos profissionais da ESF para o monitoramento dos pacientes com fatores de risco ou DRC instalada. Contudo, os exames de urina, com o objetivo de pesquisar a albuminúria/microalbuminúria, o cálculo da TFG, sendo esses importantes marcadores para avaliar a progressão da doença renal, não são solicitados com a mesma frequência 8 . Esses dados corroboram com o identificado no presente estudo em que 96% dos prontuários apresentam o registro dos resultados de creatinina, em relação à 57% de registros de exames de urina.…”
Section: Discussionunclassified
“…Apesar dos esforços que vêm sendo realizados em prol da melhoria na assistência aos usuários com predisposição ao desenvolvimento da DRC, o cuidado ofertado pelas equipes da APS a essas pessoas, ainda necessita de incremento. Visto as inconsistências no manejo desses usuários, como identificado em pesquisa realizada com os profissionais da APS, demonstrando baixo nível de solicitação dos exames de rastreio, dentre eles a TFG 8 . Além da identificação de déficit de conhecimento em relação aos critérios de encaminhamento à atenção especializada e a prevenção, resultando em direcionamento de pessoas nos estágios leve e moderados ao especialista, comprometendo o acesso dos casos avançados [9][10][11] .…”
Section: Introductionunclassified
“…No Brasil, por exemplo, pacientes com DRC têm acesso gratuito a todas as fases do tratamento. 37,38 Na África do Sul, 84% da população depende de assistência em saúde pública. Contudo, o modelo de financiamento é tal que as unidades públicas de saúde cobram pelo serviço em proporção à renda do paciente, sendo que indigentes não pagam.…”
Section: Subtema 3 Assistência Públicaunclassified
“…56 Outras pesquisas voltadas a países de baixa e média renda mostraram panoramas similares. 13,27 Apesar de diversos trabalhos apontarem a necessidade de melhores políticas com abordagens mais sistemáticas para enfrentamento da DRC, especialmente nos países de mais baixa renda, 20,21,30,33,34,37,38,55,56,57,59 percebe-se que, aos poucos, a questão vem ganhando a devida importância, o que tem levado vários países a buscar soluções inovadoras a serem incorporadas aos futuros protocolos e políticas para prevenção e tratamento da doença.…”
Section: Subtema 1 Aspectos Da Prevenção à Doença Renalunclassified